Thin film thermocouple fabrication and its application for real-time temperature measurement inside PEMFC. (October 2019) - Tang, Yu-Qing; Fang, Wen-Zhen; Lin, Hong; Tao, Wen-Quan
Highlights: 25 μm thick Type-T thin film thermocouples are fabricated. Micro sensors are embedded inside PEMFC to realize real-time measurement. Effects of inserting sensors on the cell performance are validated negligible. Fast response characteristic of sensors is observed inside PEMFC. Inside and outside temperature distribution of PEMFC are compared. Abstract: Temperature distribution in proton exchange membrane fuel cell (PEMFC) is of great importance to water and thermal management. In this study, 25 μm thick Type-T thin film thermocouples (TFTCs) were fabricated using micro-electro-mechanical system (MEMS) to realize the real-time measurement of temperature distribution inside PEMFC. Besides, fifteen sheathed thermocouples were used to measure the temperature distribution outside the cell. The effect of inserting TFTCs on the cell performance was confirmed to be negligible. The experimental results show that the embedded TFTCs can rapidly response to temperature regime while have a minimal interference to the performance of the fuel cell. The temperature variation of the inside TFTCs with current generally has the same trend with the outside sheathed thermocouples, but with a more frequent fluctuation due to their small thermal inertia and inside complex environment. In this work, the details of MEMS-based techniques of making TFTCs and measured distribution of inside cell temperature are provided.